The professional cocktail on the confusion of the role of the journalist and the role of the public relations adviser - Norgaard Kristensen, Nete (2022)
On the basis of Keith M. Macdonald's theories of the sociology of the professions (1995) (including the professional characteristics of 'traditional occupations'- such as body of knowledge, education, trade unions, ethics and relations to the state and the market) and the traditional ideas of journalistic duties, principles and values, the focus of the article is the growing tendency towards mixing professional roles in the journalistic field. Supported by data from a survey carried out among Danish journalists in the spring of 2001, the article will demonstrate the extension of the trend in a Danish context and the professional paradoxes, problems and possibilities that arise when journalists carry out both traditional media-journalistic duties and duties within the field of public relations.